Analys Of Demand and Marketing At UMKM Robaku A Managerial Economics Perspective - Amanda, Helles; Amanulloh, Fikri Ilham; Astriantri, Eneng Wulan; Nashrulloh, Fadhlan (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2026)
Roti Kukus Robaku, a micro-enterprise in the snack food sector, has become one of the preferred choices among local consumers in Sumedang Regency and demonstrates notable demand dynamics worth examining. This study aims to understand how pricing, environmental conditions, and marketing strategies influence consumer demand and the operational UMKM. The research employs a descriptive qualitative approach through direct observation and interviews with the business owner to explore production processes, sales patterns, and consumer responses. The findings indicate that demand for Roti Kukus Robaku is strongly affected by competitive pricing, weather conditions, and the consistency of the selling location. Consumers tend to be highly sensitive to price changes, making pricing decisions directly influential on sales volume. Marketing interactions remain limited to offline direct selling, which restricts market reach and hampers brand growth. In addition, limited production equipment reduces output capacity and weakens the enterprise's ability to respond to increases in demand. These results highlight the need for Roti Kukus Robaku to strengthen its strategy in pricing, digital promotion, and operational efficiency. By adopting managerial economics principles, UMKM has the potential to enhance competitiveness, expand its market, and improve business sustainability amid increasing competition and fluctuating environmental conditions.